Nanocomposite material as well as preparation method and application thereof

By grafting hydrophilic organic polymer molecules on the surface of nanostructured inorganic materials, capillary agglomeration phenomenon is induced and super hydrophilic and super hygroscopic nanocomposites are formed, the problem of poor antibacterial effect of a single nanostructure is solved, and the rapid and effective antibacterial effect is achieved, and the advantages of environmental protection, broad spectrum and high efficiency are achieved.

CN120118258APending Publication Date: 2025-06-10THE HONG KONG POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410353976.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-07
Filing Date
2024-03-26
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing nanostructures have average mechanical sterilization effects in antibacterial applications, making it difficult to achieve rapid and effective contact with antibacterials.

Method used

By grafting hydrophilic organic polymer molecules on the surface of nanostructured inorganic materials, capillary agglomeration phenomenon is induced, and super-hydrophilic and super-hygroscopic nanocomposites are formed, using the moisture in the air to form a liquid bridge, generating sufficiently strong surface tension and Laplace pressure to destroy bacteria.

Benefits of technology

It achieves faster and more effective antibacterial effects, enhances the ability to inactivate microorganisms in aerosols, is not easy to develop drug resistance, and has the advantages of environmental protection, broad spectrum, and high efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120118258A_ABST
    Figure CN120118258A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of antibacterial materials, in particular to a nano composite material and a preparation method and application thereof. The nano composite material comprises a nano-structure inorganic material and hydrophilic organic polymer molecules grafted on the surface of the nano-structure inorganic material, and the hydrophilic organic polymer molecules can induce capillary condensation on the surface of the nano-structure inorganic material. The nano composite material disclosed by the embodiment of the invention realizes physical damage deformation on bacteria based on capillary condensation, so that the process of mechanical antibiosis is accelerated, the capacity of inactivating microorganisms in aerosol is enhanced, drug resistance is not easy to generate, and the nano composite material has the advantages of environmental protection, broad spectrum and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to U.S. Patent Application No. US 63 / 607,242, filed with the U.S. Patent Office on December 7, 2023, the entire content of which is incorporated herein by reference. Technical Field

[0002] This application belongs to the technical field of antibacterial materials, and particularly relates to a nanocomposite material, a preparation method thereof, and an application thereof. Background Art

[0003] Bacteria are starting to develop a certain degree of resistance to traditional antibiotics, highlighting the need for innovative, effective, and sustainable antibacterial strategies. Due to the continuous development speed of antibiotic resistance exceeding the launch speed of new antibiotics, once easily treatable bacterial infections have become increasingly difficult. Against this backdrop, the field of nanotechnology is a promising research area that has received much attention.

[0004] The use of nanostructures can combat bacterial colonization and proliferation and reduce bacterial infections, and has received much attention in antibacterial applications. The physical properties of the nanostructured surface can directly interact with the bacterial cell membrane, resulting in physical deformation and cell death. However, the mechanical bactericidal effect provided by a single nanostructured surface is generally average, and it is difficult to achieve rapid and effective contact antibacterial. Summary of the Invention

[0005] The purpose of this application is to provide a nanocomposite material, a preparation method thereof, and an application thereof, aiming at the technical problem of how to better improve the antibacterial performance of nanomaterials.

[0006] To achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, this application provides a nanocomposite material, comprising:

[0008] A nanostructured inorganic material and a hydrophilic organic polymer molecule grafted on the surface of the nanostructured inorganic material, and the hydrophilic organic polymer molecule can induce capillary condensation on the surface of the nanostructured inorganic material.

[0009] In some embodiments, the mass ratio range of the nanostructured inorganic material to the hydrophilic organic polymer molecule is (100 - 300):1.

[0010] In some embodiments, the nanostructured inorganic material includes at least one of titanium dioxide and zinc oxide, and the nanostructure is at least one of nanowires and nanorods; and / or,

[0011] The hydrophilic organic polymer molecule includes at least one of polyvinylpyrrolidone, polyacrylic acid, and polyvinyl alcohol.

[0012] In some embodiments, the nanostructured inorganic material and the hydrophilic organic polymer molecules are connected by a silane coupling agent.

[0013] In some embodiments, the silane coupling agent includes at least one of an amino silane coupling agent, a mercapto silane coupling agent, an epoxy silane coupling agent, and a methacryloxy silane coupling agent.

[0014] In a first aspect, the present application provides a method for preparing the above-mentioned nanocomposite material, and the preparation method includes:

[0015] Providing the nanostructured inorganic material;

[0016] Grafting the hydrophilic organic polymer molecules onto the surface of the nanostructured inorganic material.

[0017] In some embodiments, the step of grafting the hydrophilic organic polymer molecules onto the surface of the nanostructured inorganic material includes:

[0018] Performing an oxygen etching treatment on the nanostructured inorganic material, then successively soaking it in a silane coupling agent solution and a photoinitiator solution, drying it, and then placing it in a hydrophilic monomer solution for ultraviolet light polymerization reaction to form the hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material.

[0019] In some embodiments, in the oxygen etching treatment, the air pressure of the oxygen atmosphere is 1 mT to 10 mT, and the etching time is 10 s to 180 s; and / or,

[0020] The time of the ultraviolet light polymerization reaction is 1 h to 3 h.

[0021] In some embodiments, the successive soaking treatment in the silane coupling agent solution and the photoinitiator solution includes: first soaking in the silane coupling agent solution for 2 h to 4 h, and then soaking in the photoinitiator solution for 10 min to 20 min.

[0022] In some embodiments, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.5% to 1%; and / or,

[0023] The mass concentration of the photoinitiator in the photoinitiator solution is 0.01 to 0.5 g / ml; and / or,

[0024] The mass concentration of the hydrophilic monomer in the hydrophilic monomer solution is 0.1 to 2 g / ml.

[0025] In some embodiments, the hydrophilic monomer in the hydrophilic monomer solution includes at least one of vinylpyrrolidone, acrylic acid, and vinyl alcohol.

[0026] In a third aspect, the present application provides an application, that is, the use of the nanocomposite provided in the first aspect of the present application and / or the nanocomposite prepared by the preparation method provided in the second aspect of the present application as an antibacterial material.

[0027] The nanocomposite provided in the first aspect of the embodiments of the present application, based on the fact that hydrophilic organic polymer molecules grafted on the surface of nanostructured inorganic materials can induce capillary condensation, has the characteristics of superhydrophilicity and super hygroscopicity. When approaching microorganisms such as bacteria, moisture in the air can form a liquid bridge in the confined space between the nanostructure and the bacteria, generating a sufficiently strong surface tension and Laplace pressure, thereby causing fluid strain and elimination of the target bacteria. The nanocomposite of the embodiments of the present application realizes physical damage and deformation of bacteria based on vapor condensation, which can accelerate the process of mechanical antibacterial, enhance the ability to inactivate microorganisms in aerosols, and not only is not prone to generating drug resistance, but also has the advantages of environmental protection, broad spectrum, and high efficiency.

[0028] The preparation method provided in the second aspect of the embodiments of the present application prepares a nanocomposite capable of inducing capillary condensation by grafting hydrophilic organic polymer molecules on the surface of nanostructured inorganic materials. The preparation method of the present application is not only simple in process, but also the obtained nanocomposite has good antibacterial properties.

[0029] The application provided in the third aspect of the embodiments of the present application is based on the fact that the nanocomposite of the present application has the function of inducing capillary condensation, and thus can be well used as an antibacterial material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0031] Figure 1 It is a schematic diagram of the mechanism of enhancing the sterilization of bioaerosols by fluid strain induced by capillary condensation of the nanocomposite of the embodiments of the present application;

[0032] Figure 2 It is a comparison diagram of the water contact angles of the nanocomposite of the embodiments of the present application and the unmodified conventional nanostructured material; among them, the superhydrophilic nanostructure of the nanocomposite of the embodiments of the present application makes the contact angle of water droplets on this surface close to 0°, while the contact angle of the unmodified conventional nanostructure is about 8°;

[0033] Figure 3 It is a comparison diagram of the time required for antibacterial of the nanocomposite of the embodiments of the present application and the unmodified conventional nanostructured material;

[0034] Figure 4 Optical photographs and SEM images of the nanocomposite material of the embodiments of the present application for PP masks;

[0035] Figure 5 Colony forming units of Escherichia coli on PP masks of the nanocomposite material of the embodiments of the present application and unmodified conventional nanostructured materials, and corresponding sample photos;

[0036] Figure 6 SEM images of the nanocomposite material of the embodiments of the present application for polyethylene terephthalate fabrics and nylon fabrics;

[0037] Figure 7 Antibacterial results of Escherichia coli of the nanocomposite material of the embodiments of the present application and unmodified conventional nanostructured materials in polyethylene terephthalate fabrics and nylon fabrics. Detailed implementation manners

[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer and more understandable, the present application will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0039] In the present application, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist simultaneously, and B exists alone. Wherein A and B may be singular or plural. The character " / " generally represents an "or" relationship between the associated objects before and after.

[0040] In the present application, "at least one" means one or more, and "a plurality" means two or more. "At least one of the following" or its similar expression refers to any combination of these items, including any combination of single item (s) or plural item (s).

[0041] It should be understood that in various embodiments of the present application, the order numbers of the above processes do not mean the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined according to its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of the present application.

[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "the" and "said" used in the embodiments of the present application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0043] In the description of the embodiments of the present application, the weights of the relevant components mentioned not only can refer to the specific contents of each component, but also can represent the proportional relationships of the weights among the components. Therefore, as long as the contents of the relevant components in the description of the embodiments of the present application are enlarged or reduced in proportion, they are within the scope disclosed in the description of the embodiments of the present application. Specifically, the mass described in the description of the embodiments of the present application can be mass units well-known in the chemical industry such as μg, mg, g, kg, etc.

[0044] The terms "first" and "second" are only used for descriptive purposes, used to distinguish objects such as substances from each other, and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX can also be referred to as the second XX. Similarly, the second XX can also be referred to as the first XX. Thus, the features defined with "first" and "second" can explicitly or implicitly include one or more of such features.

[0045] The use of the surface of nanostructures can combat bacterial colonization and proliferation and reduce bacterial infection, which has attracted much attention in antibacterial applications. Due to the unique physical properties of the nanostructured surface, it can be adjusted to produce enhanced antibacterial effects. Specifically, nanoscale features (such as nanorods, nanocones, and nanowires) can directly interact with the bacterial cell membrane, resulting in physical deformation and cell death. However, the mechanical bactericidal effect provided by a single nanostructured surface is generally average, and it is difficult to achieve rapid and effective contact antibacterial.

[0046] Capillary condensation is a natural phenomenon, generally referring to the fact that the gas in the confined space of a capillary channel can condense and transform into a liquid state without having to reach the supersaturated state. The capillary condensation phenomenon can be used to achieve various applications such as water collection in a dry environment, controllable water transport, and nanostructure assembly. According to the Kelvin formula and numerous scientific studies, on small-scale structures, even if the saturated vapor pressure is not reached, liquid can still undergo capillary condensation.

[0047] Therefore, in order to overcome the defects of a single nanostructure in the embodiments of the present application, by utilizing the capillary condensation phenomenon, hydrophilic organic polymer molecules are grafted onto the surface of the nanostructured inorganic material. The modified nanostructure has the characteristics of superhydrophilicity and super hygroscopicity. By inducing the capillary condensation effect, the target microorganisms are deformed and destroyed, thus having a better antibacterial effect. The specific scheme is as follows.

[0048] The first aspect of the embodiments of the present application provides a nanocomposite material, including: (1) nanostructured inorganic materials, that is, inorganic materials with nanostructures; (2) hydrophilic organic polymer molecules, that is, polymer organic polymers with hydrophilic properties; the hydrophilic organic polymer molecules are grafted on the surface of the nanostructured inorganic materials, which can induce capillary condensation, so that the surface of the nanocomposite material has superhydrophilic properties and forms a superhydrophilic nanostructure.

[0049] The embodiments of the present application design a nanostructured surface antibacterial strategy based on capillary condensation, which has good economic and social benefits. Specifically, as Figure 1 shown, in the structure of the superhydrophilic nanocomposite material of the embodiments of the present application, grafting hydrophilic organic polymer molecules on the surface of the nanostructured inorganic materials can induce capillary condensation, so that water in the air forms a liquid bridge in the confined space between the superhydrophilic nanostructure and bacteria, generating strong enough surface tension and Laplace pressure, thereby performing fluid strain and elimination on the target bacteria. The nanocomposite material of the embodiments of the present application can accelerate the process of mechanical antibacterial and enhance the ability to inactivate microorganisms in aerosols. It not only does not easily produce drug resistance, but also has the advantages of environmental protection, broad spectrum, and high efficiency.

[0050] It should be noted that the superhydrophilic property refers to a property that is extremely easy to be wetted when the contact angle of water droplets on the surface of the material approaches 0° due to the existence of a nanocomposite structure. Specifically, the contact angle can be less than 5°, such as 0° - 5°, and further 0° - 3°, 0° - 1°. As Figure 2 shown, the structure of the superhydrophilic nanocomposite material of the embodiments of the present application makes the contact angle of water droplets on the surface approach 0°, having superhydrophilic properties; while the contact angle of the single nanostructure without modification by hydrophilic organic polymer molecules is about 8°, and there is no superhydrophilic property.

[0051] In some embodiments, the mass ratio range of the nanostructured inorganic materials to the hydrophilic organic polymer molecules in the nanocomposite material is (100 - 300):1. Exemplarily, the mass ratio of the nanostructured inorganic materials to the hydrophilic organic polymer molecules can be ratios such as 100:1, 120:1, 150:1, 180:1, 200:1, 250:1, 300:1, etc. Modifying and grafting the hydrophilic organic polymer molecules on the surface of the nanostructured inorganic materials in the above mass ratio can better form a superhydrophilic nanostructure.

[0052] In some embodiments, the nanostructured inorganic materials in the nanocomposite material include at least one of titanium dioxide and zinc oxide, and the nanostructure is at least one of nanowires and nanorods; for example, it can be one or two or more of titanium dioxide nanowires, titanium dioxide nanorods, and zinc oxide nanowires, zinc oxide nanorods, etc. The nanostructured inorganic materials can have rigid or flexible structures.

[0053] In some embodiments, the hydrophilic organic polymer molecules in the nanocomposite can be hydrophilic polymers formed by polymerizing hydrophilic monomers. The hydrophilic monomers contain hydrophilic groups such as hydroxyl, carboxyl, aldehyde groups, etc. Specifically, the hydrophilic organic polymer molecules include at least one of polyvinylpyrrolidone, polyacrylic acid, and polyvinyl alcohol.

[0054] In some embodiments, the nanostructured inorganic material in the nanocomposite is connected to the hydrophilic organic polymer molecules through a silane coupling agent. The silane coupling agent can better connect the hydrophilic organic polymer molecules to the nanostructured inorganic material, enhancing the bonding strength at the material interface.

[0055] In some embodiments, the silane coupling agent includes at least one of an amino silane coupling agent, a mercapto silane coupling agent, an epoxy silane coupling agent, and a methacryloxy silane coupling agent. Exemplarily, the amino silane coupling agent includes 3-aminopropyltrimethoxysilane (APS), N-(2-aminoethyl)-3-aminopropylmethoxysilane (AAPS), etc., the mercapto silane coupling agent such as γ-mercaptopropyltriethoxysilane, etc., the epoxy silane coupling agent can include 3-(2,3-epoxypropoxy)propyltrimethoxysilane (A-187), γ-glycidyletheroxypropyltrimethoxysilane, etc., and the methacryloxy silane coupling agent can include γ-(methacryloxy)propyltrimethoxysilane (KH-570), etc.

[0056] The second aspect of the embodiments of the present application provides a method for preparing the above-mentioned nanocomposite, including the following steps:

[0057] S01: Provide a nanostructured inorganic material;

[0058] S02: Graft hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material.

[0059] The embodiments of the present application graft hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material, thereby preparing a nanocomposite that can induce capillary condensation. The process is not only simple, but also the obtained nanocomposite has good antibacterial properties.

[0060] Step S01: The provided nanostructured inorganic material can be at least one of nanostructured titanium dioxide and zinc oxide, such as nanowires, nanorods, etc. It can be purchased from the market or synthesized by conventional technical methods in the art.

[0061] In step S02, the step of grafting hydrophilic organic polymer molecules onto the surface of the nanostructured inorganic material includes: subjecting the nanostructured inorganic material to oxygen etching treatment, then successively soaking it in a silane coupling agent solution and a photoinitiator solution, drying it, and then placing it in a hydrophilic monomer solution for ultraviolet light-induced polymerization reaction to generate hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material.

[0062] First, oxygen etching is performed on the surface of the nanostructured inorganic material, so that it can be better modified by the silane coupling agent to graft hydrophilic organic polymer molecules. After the oxygen-etched nanostructured inorganic material is soaked in the silane coupling agent solution, it is then soaked in the photoinitiator solution to adhere the photoinitiator, and then placed in the hydrophilic monomer solution for ultraviolet light-induced polymerization reaction. In this way, under the action of light initiation, hydrophilic organic polymer molecular chains are generated by the polymerization of hydrophilic monomers, thereby generating hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material.

[0063] In some embodiments, in the oxygen etching treatment, the air pressure of the oxygen atmosphere is 1 mT to 10 mT, and the etching time is 10 s to 180 s; exemplarily, the air pressure of the oxygen atmosphere can be 1 mT, 2 mT, 5 mT, 8 mT, 10 mT, etc., and the etching time can be 10 s, 20 s, 50 s, 60 s, 80 s, 100 s, 120 s, 140 s, 160 s, 170 s, 180 s, etc. The etching effect is better under such oxygen pressure and time conditions.

[0064] In some embodiments, the step of successively soaking the nanostructured inorganic material treated by oxygen etching in the silane coupling agent solution and the photoinitiator solution includes: first soaking it in the silane coupling agent solution for 2 h to 4 h, and then soaking it in the photoinitiator solution for 10 min to 20 min. Exemplarily, the soaking time in the silane coupling agent solution can be 2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.5 h, 3.8 h, 4 h, etc., and the soaking time in the photoinitiator solution can be 10 min, 12 min, 14 min, 18 min, 20 min, etc.; a longer soaking time in the silane coupling agent solution is more conducive to the modification by the silane coupling agent.

[0065] In some embodiments, the time of the ultraviolet light-induced polymerization reaction is 1 h to 3 h. Exemplarily, the time of the polymerization reaction can be 1 h, 1.2 h, 1.6 h, 2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, etc. Hydrophilicity can be fully polymerized to generate hydrophilic organic polymer molecules within this time range.

[0066] In some embodiments, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.5% to 1%. Exemplarily, it can be 0.5%, 0.6%, 0.8%, 1%, etc. The solvent in the silane coupling agent solution can be a mixed solvent of solvent water and an alcohol solvent (such as ethanol). The mass concentration of the photoinitiator in the photoinitiator solution is 0.01 to 0.5 g / ml. Exemplarily, it can be 0.01 g / ml, 0.05 g / ml, 0.08 g / ml, 0.1 g / ml, 0.15 g / ml, 0.2 g / ml, 0.25 g / ml, 0.3 g / ml, 0.4 g / ml, 0.45 g / ml, 0.5 g / ml, etc. The solvent in the photoinitiator solution can be an alcohol solvent such as ethanol. The mass concentration of the hydrophilic monomer in the hydrophilic monomer solution is 0.1 to 2 g / ml. Exemplarily, it can be 0.1 g / ml, 0.4 g / ml, 0.8 g / ml, 1 g / ml, 1.2 g / ml, 1.5 g / ml, 2 g / ml, etc. The solvent in the hydrophilic monomer solution can be water.

[0067] Further, the silane coupling agent in the silane coupling agent solution corresponds to at least one of the above-mentioned amino silane coupling agent, mercapto silane coupling agent, epoxy silane coupling agent, and methacryloxy silane coupling agent. The photoinitiator in the photoinitiator solution can be a benzophenone-based photoinitiator such as benzophenone and 4-methylbenzophenone. The hydrophilic monomer in the hydrophilic monomer solution includes at least one of 1-vinyl-2-pyrrolidone (NVP), acrylic acid, and vinyl alcohol.

[0068] Specifically, the above process can include: putting the nanostructured inorganic material into an inductively coupled plasma (ICP) etcher and etching in an oxygen atmosphere; then soaking in the silane coupling agent solution and drying; then soaking in the photoinitiator solution and drying again; then immersing in the hydrophilic monomer solution and irradiating with ultraviolet light for polymerization to obtain a superhydrophilic and superhygroscopic nanocomposite material.

[0069] The third aspect of the embodiments of the present application provides an application, that is, the application of the nanocomposite material provided in the first aspect of the embodiments of the present application and / or the nanocomposite material prepared by the preparation method provided in the second aspect of the embodiments of the present application as an antibacterial material. Based on the nanocomposite material of the embodiments of the present application having an induced capillary condensation effect, it can kill bacteria by the method of condensing water molecules in the air, and thus can be well used as an antibacterial material.

[0070] Exemplarily, the embodiments of the present application can be used as an antibacterial material against pathogenic bacteria such as Escherichia coli and Staphylococcus aureus.

[0071] Exemplarily, the nanocomposite material of the embodiments of the present application is used as an antibacterial material in PP (polypropylene) masks, or in products such as polyethylene terephthalate fabrics and nylon fabrics.

[0072] The following is an illustration with specific embodiments.

[0073] Example 1

[0074] A nanocomposite material includes zinc oxide nanorods and polyvinylpyrrolidone grafted on the surface of the zinc oxide nanorods. The preparation method of the nanocomposite material includes:

[0075] (1) Obtain nanostructured inorganic materials (zinc oxide nanorods)

[0076] Synthesize zinc oxide nanorods by hydrothermal method. Dissolve 3.3 g of zinc acetate and 0.915 g of ethanolamine in 30 g of ethylene glycol methyl ether, stir for 3 hours until no precipitate remains to obtain a ZnO seed solution. Dissolve zinc nitrate hexahydrate (2.975 g) and hexamethylenetetramine (1.4 g) in 1 L of deionized water. After ultrasonic treatment, a transparent ZnO growth solution is obtained. Immerse the substrate in deionized water and ethanol in sequence, ultrasonically clean for 15 minutes each time, and dry for standby. Next, spin-coat the ZnO seed solution on a glass slide and cure it on a hot stage at 230 °C for 15 minutes. Finally, immerse it in the ZnO growth solution, heat at 85 °C for 9 hours, wash with deionized water and air-dry to obtain zinc oxide nanorod materials.

[0077] (2) Chemically graft polyvinylpyrrolidone to form a nanocomposite material with a superhydrophilic surface nanostructure

[0078] Put the zinc oxide nanorods (2 g) obtained in the above step into an inductively coupled plasma etcher and etch for 180 s in an oxygen atmosphere of 10 mT. Immerse the etched zinc oxide nanorods in a 1% KH-570 solution for 4 h and then dry. Immerse the KH-570-treated zinc oxide nanorods in a benzophenone ethanol solution with a concentration of 0.05 g / ml for 15 minutes and then dry again. Subsequently, immerse it in a 1-vinyl-2-pyrrolidone monomer solution with a concentration of 1 g / ml and irradiate with ultraviolet light for polymerization for 2 h to generate polyvinylpyrrolidone (0.02 g) grafted on the surface of the zinc oxide nanorods, obtaining a nanocomposite material.

[0079] Example 2

[0080] A nanocomposite material includes titanium dioxide nanowires and polyvinylpyrrolidone grafted on the surface of the titanium dioxide nanowires. The preparation method of the nanocomposite material includes:

[0081] (1) Obtain nanostructured inorganic materials (titanium dioxide nanowires)

[0082] Add 0.03 mol / L titanium tetrachloride to a concentrated hydrochloric acid solution with a mass percentage concentration of 5% to obtain a reaction solution. Immerse the substrate successively in deionized water and ethanol, ultrasonically clean for 15 minutes each time, and dry for standby. Place the substrate in the reaction solution, heat at 120 °C for 6 hours, and grow titanium dioxide nanowires on the substrate through a hydrothermal reaction.

[0083] (2) Chemically graft polyvinylpyrrolidone to form a nanocomposite with a superhydrophilic nanostructure on the surface

[0084] Put the titanium dioxide nanowires (3 g) obtained in the above steps into an inductively coupled plasma etcher and etch in an oxygen atmosphere of 10 mT for 120 s. Immerse the etched titanium dioxide nanowires in a 1% KH-570 solution for 3 h and then dry. Immerse the titanium dioxide nanowires treated with KH-570 in a benzophenone ethanol solution with a concentration of 0.08 g / ml for 15 minutes and then dry again. Subsequently, immerse it in a 1-vinyl-2-pyrrolidone monomer solution with a concentration of 1.5 g / ml and irradiate with ultraviolet light for polymerization for 1.5 h to generate polyvinylpyrrolidone (0.03 g) grafted on the surface of the titanium dioxide nanowires to obtain a nanocomposite.

[0085] Example 3

[0086] A nanocomposite includes zinc oxide nanorods and polyacrylic acid grafted on the surface of the zinc oxide nanorods. The preparation method of this nanocomposite is different from that of Example 1 in that the 1-vinyl-2-pyrrolidone monomer is replaced with an acrylic acid monomer, and other steps and parameters are the same as those in Example 1.

[0087] Example 4

[0088] A nanocomposite includes titanium dioxide nanowires and polyacrylic acid grafted on the surface of the titanium dioxide nanowires. The preparation method of this nanocomposite is different from that of Example 2 in that the 1-vinyl-2-pyrrolidone monomer is replaced with an acrylic acid monomer, and other steps and parameters are the same as those in Example 2.

[0089] Comparative Example 1

[0090] Nanocomposite of polyvinylpyrrolidone-coated titanium dioxide:

[0091] Weigh 100 g of zirconia beads with a particle size of 0.1 mm and pour them into a 100 ml ball mill jar. Weigh 3 g of anatase-type nano-titanium dioxide powder and 0.03 g of polyvinylpyrrolidone, place them in a 100 ml ball mill jar, then add 50 g of pure water to the ball mill jar, place it in a ball mill, set the ball mill speed to 800 r / min, and the time to 1 h. After the ball milling is completed and cooled, centrifuge the nano-titanium dioxide colloidal solution coated with polyvinylpyrrolidone, and after drying, the obtained powder is the nano-composite material [wherein polyvinylpyrrolidone forms a coating layer].

[0092] Antibacterial performance test of nano-composite materials

[0093] The test steps include: (1) Cultivate Staphylococcus aureus and Escherichia coli respectively to prepare corresponding bacterial solutions. Transfer the single bacterial colonies on the solid Luria-Bertani agar plate to 10 mL of Luria-Bertani broth and culture at 37 °C for 24 h. Wash the bacterial solution with phosphate buffer (PBS) and collect by centrifugation. Redisperse the bacterial precipitate with PBS to prepare a suspension for further experiments. Measure the bacterial concentration by serial dilution and CFU counting. Add 5 mL of the bacterial solution (10 7 CFU / mL) to a compressed nebulizer to generate bioaerosols. (2) Spray the bacterial-containing aerosol (10 7 CFU / mL) onto the surface of the sample prepared in the above example at a distance of 25 cm for 30 seconds, and allow it to contact Escherichia coli and Staphylococcus aureus for a certain time. Subsequently, transfer the bacteria to the agar plate by ultrasonic wave and spread them, and then incubate the plate at 37 °C for 24 h to evaluate the antibacterial performance.

[0094] Table 1

[0095]

[0096] Note: The data in Table 1 are averaged over 5 times. In addition, a blank group (referring to no nano-composite material and no single nano-structure) and a single nano-structure (referring to a nano-structured inorganic material without grafted and modified hydrophilic polymer molecules: zinc oxide nanorods) are set.

[0097] The results are as shown in Table 1 above and Figure 3 as shown. It shows that the synergistic effect of the mechanical antibacterial mechanism and the capillary condensation antibacterial mechanism induced by the super-hydrophilic and super-hydroscopic surface of the nano-composite material in the examples of this application improves the antibacterial efficiency and enhances the antibacterial effect.

[0098] Application test of nano-composite materials

[0099] (1) Apply the nano-composite material prepared in Example 1 to a PP mask

[0100] Material preparation steps and colony testing steps in the specific application process:

[0101] Material preparation steps: Synthesize zinc oxide nanorods by hydrothermal method. Dissolve 3.3 g of zinc acetate and 0.915 g of ethanolamine in 30 g of ethylene glycol methyl ether, stir for 3 hours until no precipitate remains, and obtain a ZnO seed solution. Dissolve zinc nitrate hexahydrate (2.975 g) and hexamethylenetetramine (1.4 g) in 1 L of deionized water. After ultrasonic treatment, a transparent ZnO growth solution is obtained. Next, immerse the polyethylene (PP) melt-blown cloth in the ZnO seed solution and cure it on a hot plate at 100 °C for 15 minutes. Finally, immerse it in the ZnO growth solution, heat it at 85 °C for 12 hours, wash it with deionized water and air-dry it. Put the polyethylene (PP) melt-blown cloth modified with zinc oxide nanorods obtained from the above steps into an inductively coupled plasma etcher and etch it in an oxygen atmosphere of 10 mT for 60 s. Immerse the etched zinc oxide nanorods in a 1% KH-570 solution for 4 h and then dry. Immerse the zinc oxide nanorods treated with KH-570 in a benzophenone ethanol solution with a concentration of 0.05 g / ml for 15 minutes and then dry again. Subsequently, immerse it in a 1-vinyl-2-pyrrolidone monomer solution with a concentration of 1 g / ml and irradiate it with ultraviolet light for polymerization for 2 h to generate polyvinylpyrrolidone, and obtain a polyethylene (PP) melt-blown cloth modified with nanocomposites. The results are as Figure 4 shown. Scanning electron microscope pictures show that nanocomposites are modified on the PP melt-blown cloth fibers.

[0102] Antibacterial testing steps: (1) Culture Escherichia coli and prepare the corresponding bacterial solution. Transfer the single bacterial colony on the solid Luria-Bertani agar plate to 10 mL of Luria-Bertani broth and culture it at 37 °C for 24 h. Wash the bacterial solution with phosphate buffer (PBS) and collect it by centrifugation. Redisperse the bacterial precipitate with PBS to prepare a suspension for further experiments. Measure the bacterial concentration by serial dilution and CFU counting. Add 5 mL of the bacterial solution (10 7 CFU / mL) to a compression nebulizer to generate bioaerosols. (2) Spray the bacterial-containing aerosol (10 7 CFU / mL) onto the surface of the sample of the above polyethylene (PP) melt-blown cloth modified with nanocomposites at a distance of 25 cm for 30 s and let it contact Escherichia coli for a certain time. Subsequently, transfer the bacteria to the agar plate by ultrasound and spread it, and then incubate the plate at 37 °C for 24 h to evaluate the antibacterial performance.

[0103] The antibacterial results are as Figure 5As shown: The blank group is an unmodified PP meltblown fabric, and the single nanostructure refers to a PP meltblown fabric modified with zinc oxide nanorods without grafted hydrophilic polymer molecules; The results show that after the PP meltblown fabric modified with the superhydrophilic nanocomposite of the examples of the present application was in contact with Escherichia coli for six minutes, no colonies were formed and all bacteria were killed, indicating its excellent antibacterial effect.

[0104] (2) Apply the nanocomposite prepared in Example 1 to polyethylene terephthalate (PET) fabrics and nylon fabrics

[0105] Specific material preparation steps and colony test steps in the application process:

[0106] Material preparation steps: Synthesize zinc oxide nanorods by hydrothermal method. Dissolve 3.3 grams of zinc acetate and 0.915 grams of ethanolamine in 30 grams of ethylene glycol monomethyl ether, stir for 3 hours until no precipitate remains to obtain a ZnO seed solution. Dissolve zinc nitrate hexahydrate (2.975 g) and hexamethylenetetramine (1.4 g) in 1 L of deionized water. After ultrasonic treatment, a transparent ZnO growth solution is obtained. Next, immerse polyethylene terephthalate (PET) fabrics and nylon fabrics in the ZnO seed solution and cure them on a hot plate at 100 °C for 15 minutes. Finally, immerse them in the ZnO growth solution, heat at 85 °C for 12 hours, wash with deionized water and air dry. Put the zinc oxide nanorods (2 g) obtained in the above steps into an inductively coupled plasma etcher and etch in a 10 mT oxygen atmosphere for 60 s. Immerse the etched zinc oxide nanorods in a 1% KH-570 solution for 4 h and then dry. Immerse the KH-570-treated zinc oxide nanorods in a 0.05 g / ml benzophenone ethanol solution for 15 minutes and then dry again. Subsequently, immerse them in a 1 g / ml 1-vinyl-2-pyrrolidone monomer solution and irradiate with ultraviolet light for polymerization for 2 h to generate polyvinylpyrrolidone, obtaining polyethylene terephthalate (PET) fabrics and nylon fabrics modified with the nanocomposite, and the morphology characterization results are as Figure 6 shown.

[0107] Antibacterial test steps: (1) Cultivate Escherichia coli and prepare the corresponding bacterial solution. Transfer the bacterial single colony on the solid Luria-Bertani agar plate to 10 mL of Luria-Bertani broth and culture at 37 °C for 24 h. Wash the bacterial solution with phosphate buffer (PBS) and collect by centrifugation. Redisperse the bacterial precipitate with PBS to prepare a suspension for further experiments. Measure the bacterial concentration by serial dilution and CFU counting. Add 5 mL of the bacterial solution (10 7(CFU / mL) was added to a compression nebulizer to generate bioaerosols. (2) The bacterial aerosol (10 7 CFU / mL) was sprayed onto the surfaces of the above-mentioned nanocomposite-modified polyethylene terephthalate (PET) fabric and nylon fabric samples at a distance of 25 cm for 30 seconds, and allowed to contact Escherichia coli for a certain period of time. Subsequently, the bacteria were transferred to an agar plate by ultrasonic wave and spread, and then the plate was incubated at 37 °C for 24 h to evaluate the antibacterial performance.

[0108] The antibacterial results are as Figure 7 shown: The blank group is the unmodified polyethylene terephthalate fabric / nylon fabric, and the single nanostructure refers to the polyethylene terephthalate fabric / nylon fabric modified with zinc oxide nanorods without grafting hydrophilic polymer molecules; the results show that after the superhydrophilic nanocomposite-modified polyethylene terephthalate (PET) fabric and nylon fabric of the examples of the present application contacted Escherichia coli for six minutes, no colonies were formed and all the bacteria were killed, indicating that it has excellent antibacterial effects.

[0109] The above are only the preferred embodiments of the present application, and are not intended to limit the present application. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A nanocomposite material, characterized in that: include: A nanostructured inorganic material and hydrophilic organic polymer molecules grafted on the surface of the nanostructured inorganic material, wherein the hydrophilic organic polymer molecules can induce capillary condensation on the surface of the nanostructured inorganic material.

2. The nanocomposite material according to claim 1, characterized in that The mass ratio of the nanostructured inorganic material to the hydrophilic organic polymer molecules is in the range of (100-300):

1.

3. The nanocomposite material according to claim 1, characterized in that The nanostructured inorganic material comprises at least one of titanium dioxide and zinc oxide, and the nanostructure is at least one of nanowires and nanorods; and / or, The hydrophilic organic polymer molecules include at least one of polyvinyl pyrrolidone, polyacrylic acid and polyvinyl alcohol.

4. The nanocomposite material according to any one of claims 1 to 3, characterized in that The nanostructured inorganic material and the hydrophilic organic polymer molecules are connected via a silane coupling agent.

5. The nanocomposite material according to claim 4, characterized in that The silane coupling agent includes at least one of an aminosilane coupling agent, a mercaptosilane coupling agent, an epoxysilane coupling agent and a methacryloxysilane coupling agent.

6. A method for preparing a nanocomposite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Providing the nanostructured inorganic material; The hydrophilic organic polymer molecules are grafted onto the surface of the nanostructured inorganic material.

7. The preparation method according to claim 6, characterized in that: The step of grafting the hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material comprises: The nanostructured inorganic material is subjected to oxygen etching treatment, then immersed in a silane coupling agent solution and a photoinitiator solution in sequence, dried, and then placed in a hydrophilic monomer solution for ultraviolet light polymerization reaction to generate the hydrophilic organic polymer molecules on the surface of the nanostructured inorganic material.

8. The preparation method according to claim 7, characterized in that: In the oxygen etching process, the pressure of the oxygen atmosphere is 1mT to 10mT, and the etching time is 10s to 180s; and / or, The ultraviolet light polymerization reaction time is 1h to 3h.

9. The preparation method according to claim 7, characterized in that: The sequential immersion treatment in the silane coupling agent solution and the photoinitiator solution includes: first immersing in the silane coupling agent solution for 2 hours to 4 hours, and then immersing in the photoinitiator solution for 10 minutes to 20 minutes.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The mass concentration of the silane coupling agent in the silane coupling agent solution is 0.5% to 1%; and / or, The mass concentration of the photoinitiator in the photoinitiator solution is 0.01 to 0.5 g / ml; and / or, The mass concentration of the hydrophilic monomer in the hydrophilic monomer solution is 0.1 g / ml to 2 g / ml.

11. The preparation method according to any one of claims 7 to 9, characterized in that: The hydrophilic monomer in the hydrophilic monomer solution includes at least one of vinyl pyrrolidone, acrylic acid and vinyl alcohol.

12. Use of the nanocomposite material according to any one of claims 1 to 5 and / or the nanocomposite material prepared by the preparation method according to any one of claims 6 to 11 as an antibacterial material.